Large-particle distribution at time series station DYFAMED - Lars Stemmann; G Gorsky; Jean-Claude Marty; Marc Picheral; Juan Carlos Miquel (PANGAEA, 2002)
Data on large particles (LP; >0.15 mm), phytoplankton communities, vertical fluxes, and hydrology were collected between January 1992 and June 1996 in the NW Mediterranean Sea, during DYFAMED, an interdisciplinary program part of JGOFS France. LP concentrations at the study sites were typical for values found in other open-ocean studies. LP temporal evolution showed an annual cycle. Concentrations were the highest in winter/spring (20-120/l, 5-280 mg/m**3) and lowest in summer and autumn (0-20/l, 0.8-60 mg/m**3). We estimated that LP accounted on average, for 2-30% of the total particulate (>0.7 μm) dry weight (DW). LP temporal evolution between 0-200 m was correlated with total Chl a and fucoxanthin (diatoms), and inversely correlated to zeaxanthin (cyanobacteria and prochlorophytes). Although diatoms were clearly associated to LP, prymnesiophytes were associated to the two highest accumulation of particles >1 mm. The DW fraction of particle >0.5 mm to total LP increased from 10% in regenerated systems dominated by picoplankton to 50% during spring blooms. LP concentrations in the upper 200 m were correlated to mass flux recorded in sediment trap at 200 and 1000 m. We defined three main periods for LP downward export related to physical stratification. (1) The major LP export occurred in winter and may be affected by deep vertical mixing; (2) in spring, at the onset of the thermal stratification LP downward export decreased, although pulses of phytoplanktonic production may have enhanced LP sedimentation over short time scales; (3) during the summer stratification, the deep water was generally depleted in LP.
Supplement to: Stemmann, L et al. (2002): Four-year study of large-particle vertical distribution (0–1000 m) in the NW Mediterranean in relation to hydrology, phytoplankton, and vertical flux. Deep Sea Research Part II: Topical Studies in Oceanography, 49(11), 2143-2162, https://doi.org/10.1016/S0967-0645(02)00032-2